2020
DOI: 10.1002/jmv.25722
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of COVID‐19 based on current evidence

Abstract: Since December 2019, a series of unexplained pneumonia cases have been reported in Wuhan, China. On 12 January 2020, the World Health Organization (WHO) temporarily named this new virus as the 2019 novel coronavirus (2019‐nCoV). On 11 February 2020, the WHO officially named the disease caused by the 2019‐nCoV as coronavirus disease (COVID‐19). The COVID‐19 epidemic is spreading all over the world, especially in China. Based on the published evidence, we systematically discuss the characteristics of COVID‐19 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
854
2
74

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 984 publications
(944 citation statements)
references
References 24 publications
(45 reference statements)
14
854
2
74
Order By: Relevance
“…At present, systemic glucocorticoids administration was empirically used for severe comp licat ions in order to suppress CS man ifestations in patients with COVID-19, such as ARDS, acute heart in juries, acute kidney complication, and patients with higher D-d imer levels, et al [3,23,24] However, there is no evidence from randomized clinical trials to support glucocorticoids treatment for COVID-19. Chen et al reported 19 (19%) patients were treated with glucocorticoids for 3-15 days (median 5 [3][4][5][6][7]), and methylprednisolone (1-2 mg/kg per day) are reco mmended for patients with ARDS, fo r as short a duration of treatment as possible [25].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…At present, systemic glucocorticoids administration was empirically used for severe comp licat ions in order to suppress CS man ifestations in patients with COVID-19, such as ARDS, acute heart in juries, acute kidney complication, and patients with higher D-d imer levels, et al [3,23,24] However, there is no evidence from randomized clinical trials to support glucocorticoids treatment for COVID-19. Chen et al reported 19 (19%) patients were treated with glucocorticoids for 3-15 days (median 5 [3][4][5][6][7]), and methylprednisolone (1-2 mg/kg per day) are reco mmended for patients with ARDS, fo r as short a duration of treatment as possible [25].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…The novel coronavirus (SARS-CoV-2) responsible for the current pandemic of coronavirus disease (COVID-19) that originated in Wuhan, China in December 2019 has now spread to 113 countries and territories outside of China (1,2). SARS-CoV-2 is a betacoronavirus that infects humans and the disease presents mostly with fever, cough, and dyspnea (3). Healthcare workers (HCWs) are at the front-line of COVID-19 outbreak, and their constant exposure to infected patients and contaminated surfaces can put them at risk for acquiring and transmitting the infection (4).…”
mentioning
confidence: 99%
“…Those who are not immune, assuming that we do not yet have a vaccine, are a dilemma. One approach would be regular evaluation of symptoms, tracking contacts with known cases, temperature checks, and, if possible, regular viral tests (2).…”
Section: Inklingsmentioning
confidence: 99%
“…For those patients, we may implement an epidemiologic survey that would include a symptomatic evaluation, such as fever, fatigue, cough, etc. (2). A contact history for those in an endemic area may already have been gathered, and we can add our own investigation of potential infectious encounters during the preceding 14 days.…”
Section: Inklingsmentioning
confidence: 99%
See 1 more Smart Citation